Analýza ukončení pracovního poměru zaměstnance u SEVAS, spol. s r. o. - Zvolská, Michaela (Vysoké učení technické v Brně. Fakulta podnikatelská, 2015)
Bakalářská práce se zabývá ukončením pracovního poměru a návrhem optimálního řešení zaměstnání nového zaměstnance u společnosti SEVAS, spol. s r.o.

This bachelor's thesis deals with the termination of employment and design optimal employment of a new employee at the company SEVAS, spol. s r.o.
Analysis of Employment Termination in SEVAS, spol. s r. o.
Keywords: Pracovní poměr; zaměstnanec; zaměstnavatel; pracovní smlouva; zákoník práce.; Employment; employer; employee; contract of employment; labor code.